If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(9 + -8g) = 0 (9 * 3 + -8g * 3) = 0 (27 + -24g) = 0 Solving 27 + -24g = 0 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + -24g = 0 + -27 Combine like terms: 27 + -27 = 0 0 + -24g = 0 + -27 -24g = 0 + -27 Combine like terms: 0 + -27 = -27 -24g = -27 Divide each side by '-24'. g = 1.125 Simplifying g = 1.125
| Cos(5x)=(sin(5x))(sin(5x))+1 | | y=3.4x+5 | | 4x+57+(x+13)=180 | | =-3x^2-8x+6 | | 9x+14x+(x+36)=180 | | 37+(4x+6)+(x+12)=180 | | 1/3(9x-15)-2x | | (2x-12)+(6x-10)+(x+13)=180 | | (F/3)-5=1 | | 8x+6=12-48 | | [2ln(3)]^1/3 | | 3/8x-3/32 | | 3/2x-6 | | 26=-8/5h | | (2x-19)+(2x+5)+30=180 | | 5x-1=11y+3 | | 83+9x+(4x+6)=180 | | 8=-2/5g | | 17z=3 | | 2x+(3x+1)+(x+17)=180 | | 0.75k-5=0.25-1 | | 3/4f=-12 | | H/1.6=5 | | 2x^3-12x+18x=0 | | (2x+22)+(2x+34)+40=180 | | -72=8h | | 5x+2+8x+4+z=180 | | 9x+4x+(7x-40)=180 | | -10=-d/4 | | 11x+2=52 | | 4d+4= | | (5x+20)+(3x+1)+(4x+15)=180 |